THE IMPACT COVID-19 ON POVERTY LEVEL OF COMMUNITY FROM AN ISLAMIC ECONOMIC PERSPECTIVE - Ana Adiliani; R Agus Abikusna; Abdul Fatakh; Abdurokhim Abdurokhim (Politeknik Siber Cerdika Internasional, 2023)
The purpose of this research is to find out and analyze poverty in terms of the Covid-19 Pandemic and in general before the Pandemic hit Rungkang Village, and how to overcome poverty occurs through the role of government and the Islamic economy so that it can eliminate poverty. This type of research is descriptive qualitative research, and the approach used in this research is ethnographic research. The research location taken was in Rungkang Village, Losari District, Brebes Regency. The implementation time is from November 2021 to May 2022. The data taken is real data obtained from the field. Sources of data in this study were obtained from communities affected by the Covid-19 pandemic in Rungkang Village, Losari District, Brebes Regency. Data collection techniques were carried out using observation, interviews, and documentation. The data analysis technique uses interactive Milles and Huberman analysis. The results of the study show that the Covid-19 Pandemic has had an impact on changing the behavior of the people of Rungkang Village where economic activity has driven an increasing poverty rates where unemployment has reduced the economy.